Lydia S.M. Robinson collection relating to World War I - Robinson, Lydia S. M.
Correspondence, military service record data sheets, lists, notes, clippings, printed matter, a card index, and photographs relating to American citizens who joined the Allied Powers prior to the official entrance of the United States into World War I. Includes material pertaining to Americans who were rejected for military service by American recruiting officers for medical reasons or age after this country went to war but were able to enlist in one of the Allied services and to men in the Allied services who later transferred to American armed services after this country joined the Allies against the Central Powers. Consists principally of military service record data sheets providing date and place of birth, name of parents, date and place of enlistment, declaration of citizenship, outfit and branch of service, and name of country for which service was rendered.
Secretary of the Navy League of the United States, Dept. 6, Philadelphia, Pa.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Allied and Associated Powers (1914-1920); Recruiting and enlistment; World War, 1914-1918.; World War, 1914-1918 -- United States; United States -- Armed Forces